2016
DOI: 10.1080/23328940.2016.1257407
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferent activation decreases brown adipose tissue (BAT) sympathetic nerve activity and BAT thermogenesis

Abstract: In urethane/α-chloralose anesthetized rats, electrical stimulation of cervical vagal afferent fibers inhibited the increases in brown adipose tissue sympathetic nerve activity and brown adipose tissue thermogenesis evoked by cold exposure, by nanoinjection of the GABAA receptor antagonist, bicuculline, in the dorsomedial hypothalamus, and by nanoinjection of N-methyl-D-aspartate in the rostral raphe pallidus. Vagus nerve stimulation-evoked inhibition of brown adipose tissue sympathetic nerve activity was preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Therefore, NTS neurons could mediate the NPY-triggered signaling from the hypothalamus to GABAergic IRt/PCRt neurons to indirectly inhibit sympathetic premotor neurons in the rMR. Because the NTS receives a variety of vagal visceral afferents, some of which may inhibit BAT SNA (Morrison et al, 2014; Madden et al, 2016), the hypothalamic NPY signal could be integrated with nutritional visceral information impinging on NTS neurons before being transmitted to the IRt/PCRt (Figure 7I). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NTS neurons could mediate the NPY-triggered signaling from the hypothalamus to GABAergic IRt/PCRt neurons to indirectly inhibit sympathetic premotor neurons in the rMR. Because the NTS receives a variety of vagal visceral afferents, some of which may inhibit BAT SNA (Morrison et al, 2014; Madden et al, 2016), the hypothalamic NPY signal could be integrated with nutritional visceral information impinging on NTS neurons before being transmitted to the IRt/PCRt (Figure 7I). …”
Section: Discussionmentioning
confidence: 99%
“…Since then, studies carried out also in rats have identified the effect of duodenal lipid sensing, as well the effect of glucagon-like peptide-1 released from enteroendocrine cells on nonshivering brown fat thermogenesis (47,48). Work by our coauthor (CJM) (49,50) indicates that, in rats, vagal afferent activity can regulate the effect of cooling on BAT sympathetic nerve activity (SNA) and BAT thermogenesis. Given the extensive background information on vagal afferent activation and thermogenesis in BAT that was done in rat models, and our past experience with that model, we used it to determine the effect of CCK-8.…”
Section: Neurogenic Contribution Of Cck-8 To Energy Expenditure Throumentioning
confidence: 98%
“…Ghrelin can also inhibit BAT sympathetic nerve activity by acting on the vagus nerve in addition to its action in the arcuate nucleus. Intriguingly, vagus nerve stimulation inhibits BAT thermogenesis induced by glutamatergic stimulation of sympathetic premotor neurons in the rMR, but not that induced by antagonizing GABA A receptors in the rMR, indicating that, similar to the hypothalamic NPY‐triggered hunger signaling, vagal inputs to the NTS also inhibit BAT thermogenesis by stimulating GABAergic inhibition of sympathetic premotor neurons in the rMR. These findings support the possible mechanism for signal integration (Figure ), in which the vagal inputs conveying visceral nutritional information affect the medullary circuit for energy homeostasis by impinging on the NTS neurons mediating the NPY‐triggered hunger signaling from the hypothalamus to the IRt/PCRt.…”
Section: Hypothetical Model Of Hypothalamomedullary Hunger and Satietmentioning
confidence: 98%